2006
DOI: 10.7326/0003-4819-145-3-200608010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Improving Blood Pressure Control through Provider Education, Provider Alerts, and Patient Education

Abstract: A multifactorial intervention including patient education improved blood pressure control compared with provider education alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
163
0
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(176 citation statements)
references
References 40 publications
6
163
0
7
Order By: Relevance
“…The other two main reasons, "Discontinued hypertension medication when they consider has been cured" and "Discontinuation medication of long course of medical treatment", were also common causes for poor adherence investigation, often not only in hypertension. However, according to qualitative analysis studies, it was shown that poor compliance was mainly for lack of communication, which resulted in misunderstanding and a lot of subjective factors for low adherence (Roumie et al, 2006;Tsiantou et al, 2010). The top three main reasons were subjective factors and all situations could be improved by our pharmacist in the form of the practice mentioned in the methodology part.…”
Section: Discussionmentioning
confidence: 97%
“…The other two main reasons, "Discontinued hypertension medication when they consider has been cured" and "Discontinuation medication of long course of medical treatment", were also common causes for poor adherence investigation, often not only in hypertension. However, according to qualitative analysis studies, it was shown that poor compliance was mainly for lack of communication, which resulted in misunderstanding and a lot of subjective factors for low adherence (Roumie et al, 2006;Tsiantou et al, 2010). The top three main reasons were subjective factors and all situations could be improved by our pharmacist in the form of the practice mentioned in the methodology part.…”
Section: Discussionmentioning
confidence: 97%
“…Так, обучение амбулаторных пациентов, состоящих на диспансерном учете, позволяет не только достичь стойкого снижения поведенческих факторов риска, обусловленных при-вычками неправильного питания, курением, низкой дви-гательной активностью, достичь повышения привер-женности пациентов к выполнению врачебных реко-мендаций [5,9], но и сопровождается двукратным уве-личением доли пациентов, достигших целевого АД, по сравнению с обычной практикой [7,8]. Кроме того, шко-лы здоровья для пациентов с АГ экономически целе-сообразны, поскольку позволяют получить сокращение затрат на болезнь [16,17].…”
Section: Discussionunclassified
“…В многочисленных работах [4][5][6][7][8][9] показан меди-цинский эффект применения обучающих программ для пациентов с АГ, характеризующий деятельность меди-цинских работников с точки зрения достижения поло-жительного результата: снижение артериального дав-ления (АД), приверженность к выполнению врачебных рекомендаций по немедикаментозной и медикамен-тозной коррекции факторов риска сердечно-сосудистых заболеваний и АГ. Кроме того, имеются работы по со-циальной эффективности Школ здоровья, в частности, касающиеся информированности пациентов о факто-рах риска и способах их коррекции, а также касающихся социальной адаптации пациентов с хронической па-тологией, их удовлетворенности качеством медицин-ской помощи [4][5][10][11][12].…”
unclassified
“…Salzsieder and colleagues used their Diabetiva® program to apply continuous glucose monitoring (CGM) data to a DSS to improve A1C (43). Decision support systems that have been used in blood pressure management show conflicting results (44)(45).…”
Section: The Case For Systematic Rigorous Examination Of a Computer mentioning
confidence: 99%